2013
DOI: 10.3923/pjbs.2013.1776.1780
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Etiology of Subclinical Mastitis among Buffaloes (Bubalus bubalus) in Namakkal, India

Abstract: A study was carried out from February 2013 to January 2015 in 1650, buffaloes of organized and unorganized farms of Durg, Rajnandgaon, Raipur and Bilaspur districts of Chhattisgrah State in India, to determine the prevalence of subclinical mastitis. Milk samples were collected to detect subclinical mastitis in individual animal based on milk somatic cell count (SCC) and MCMT. The overall prevalence of buffalo subclinical mastitis accounted for 41.51% (685/1650). Prevalence of SCC was evaluated on the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 2 publications
9
6
0
Order By: Relevance
“…Similarly E. coli was highly resistant to ceftriaxone, trimethoprim, azithromycin and nitrofurantoine but susceptible to ciprofloxacin, azithromycin, trimethoprim, chloramphenicol and levofloxacin due to its infrequent usage ( Figure 5). Our results are consistent with the result published recently 12 . However, some risk factors should be taken into account for prevention of mastitis in buffalo 13 .…”
Section: Resultssupporting
confidence: 94%
“…Similarly E. coli was highly resistant to ceftriaxone, trimethoprim, azithromycin and nitrofurantoine but susceptible to ciprofloxacin, azithromycin, trimethoprim, chloramphenicol and levofloxacin due to its infrequent usage ( Figure 5). Our results are consistent with the result published recently 12 . However, some risk factors should be taken into account for prevention of mastitis in buffalo 13 .…”
Section: Resultssupporting
confidence: 94%
“…According to Table 1, the prevalence of SCM in dairy buffaloes was recorded as 10.13% and 10.74 % during the parity numbers 1 and 2, respectively. Srinivashan et al (2013) showed the prevalence of SCM in cows was recorded in 17.94%, 20.58%, 23.07% and 32.50% during the parity numbers 1, 2, 3 and 4 respectively which is quite similar to the current study. It has been reported that the prevalence of SCM in cows were recorded as 18.75%, 22.22%, 29.55% and 26.66% during the parity numbers 1, 2, 3 and 4, respectively (Rahman et al 1997).…”
Section: Season Wise Prevalence Of Subclinical Mastitis In Buffaloessupporting
confidence: 90%
“…It has been reported that high yielding cows are more prone to udder infection than low producing one (Hossain, 2004 andRadostits et al, 2000). Srinivashan et al (2013) also found the same results in their study. In present study, among the 21 positive cases from 200 dairy buffaloes SCM was recorded as 7(7.29%) and 14(13.46%) in the age group of 3 to 6 years and 7 to 18 years, respectively (Table 1).…”
Section: Season Wise Prevalence Of Subclinical Mastitis In Buffaloessupporting
confidence: 79%
“…Singh et al, 2013 Uttar Pradesh North 1, 2 40. Srinivasan et al, 2013 Tamil Nadu South 1, 3 41. Thakor et al, 2013 Gujarat West 1 42.…”
Section: Meta-analysis Of Subclinical and Clinical Mastitismentioning
confidence: 99%